Gravitational N-body simulations - Aarseth, Sverre J. (Sverre Johannes), 1934- (Cambridge monographs on mathematical physics., 2003)
This book presents basic methods for numerical simulation of gravitational systems, demonstrating how to develop clear and elegant algorithms. It explains the fundamental mathematical tools needed to describe the dynamics of a large number of mutually attractive particles, and the techniques needed to model various known planetary and astrophysical phenomena.